HISTORICAL DEVELOPMENT AND MODERN BIOECOLOGICAL INSIGHTS INTO THE LEPIDOPTERA FAUNA OF CENTRAL ASIA - Isaeva, Z. (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This paper provides a comprehensive examination of the chronological development, research evolution, and current bioecological understanding of butterflies belonging to the order Lepidoptera within Central Asia. Drawing upon archival sources and earlier scientific records, it traces the establishment of entomological traditions in the region and outlines recent advancements in faunistic and ecological studies. The analysis highlights key issues related to the conservation of butterfly biodiversity, anthropogenic impacts on ecosystems, and strategic priorities for forthcoming investigations.